2014
DOI: 10.1111/jfb.12368
|View full text |Cite
|
Sign up to set email alerts
|

Radiocaesium concentrations in the muscle and eggs of salmonids from Lake Chuzenji, Japan, after the Fukushima fallout

Abstract: Approximately 18 months (September to December 2012) after the Fukushima Dai-ichi Nuclear Power Plant accident, elevated radiocaesium concentrations were measured in samples of muscle and eggs from masu salmon Oncorhynchus masou, kokanee Oncorhynchus nerka, brown trout Salmo trutta and lake trout Salvelinus namaycush from the Lake Chuzenji system, central Honshu Island, Japan (160 km from the station). Mean muscle concentrations were 142·9-249·2 Bq kg⁻¹ wet mass and mean concentrations in eggs were 38·7-79·0 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In Lake Chuzenji, mean muscle radiocaesium concentrations of salmonid fishes (kokanee, masu salmon, brown trout (Salmo trutta), and lake trout (Salvelinus namaycush)) collected during September to December 2012 were in the range of 142.9-249.2 Bq·kg -1 (wet mass; Yamamoto et al 2014). In this study, substantial accumulation of radiocaesium was also confirmed in muscle tissue of hatchery-reared salmonids after release into cages set in Lake …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In Lake Chuzenji, mean muscle radiocaesium concentrations of salmonid fishes (kokanee, masu salmon, brown trout (Salmo trutta), and lake trout (Salvelinus namaycush)) collected during September to December 2012 were in the range of 142.9-249.2 Bq·kg -1 (wet mass; Yamamoto et al 2014). In this study, substantial accumulation of radiocaesium was also confirmed in muscle tissue of hatchery-reared salmonids after release into cages set in Lake …”
Section: Discussionsupporting
confidence: 64%
“…After the accident, radiocaesium contamination was quickly transferred to freshwater and marine ecosystems, which resulted in elevated radiocaesium concentrations in many fish and invertebrate species (see, for example, Buesseler 2012; Tateda et al 2013;Yamamoto et al 2014). Radiocaesium contamination in freshwater fish has received particular attention, with accumulated evidence from the Chernobyl nuclear accident (Ukraine) showing that higher concentrations of radionuclides persisted in freshwater fish from several European lakes for 10 years or more (see, for example, Jonsson et al 1999;Brittain and Gjerseth 2010;Rask et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledgments This chapter was revised from a paper published by Yamamoto et al ( 2014b ). The authors are grateful to Kouji Mutou and the Lake Chuzenji Fishermen's Cooperative for collecting the fi sh samples and to Masato Murakami, Tomoko Okazaki, Yumiko Watanuki, and Maki Yoshida for their assistance with the sample assays and data analyses.…”
mentioning
confidence: 99%